Understanding the Gap: Evaluation of General Practitioner’s Awareness and Expertise in Managing Substance Use and Addiction in South Punjab, Pakistan (Medical Forum Monthly, 2022)
Objective: To determine General practitioner’s (GPs) awareness and expertise in management of substance use disorders in southern Punjab, Pakistan.Study Design: Descriptive Cross-sectional studyPlace and Duration of Study: This study was conducted at the department of Psychiatry, Multan Medical and Dental College, Multan, from May 2020 to April 2021.Materials and Methods: One hundred and three general physicians/ practitioners practicing in public and private setups in South Punjab were interviewed for the study. A self-formulated questionnaire was filled by health care professionals. Data analysis was done by using SPSS version 23. Mean and frequency were calculated and also chi square test was applied. P value ≤0.05 was taken as significance.Results: The mean age 34.86±9.16and mean experience of PGs were7.93±6.89years. Almost all participants agreed that substance use is a serious issue. However nearly 1/3rd to ½ of the respondents could not correctly identify the classical withdrawals of opioid or disadvantages of long term use of benzodiazepines. One-third of the group was unaware that Delirium Tremens is a serious life threatening complication of Alcohol withdrawal. 71% admitted that they don’t feel confident in managing addiction related cases and more than 90% showed willingness to attend workshops and CMEs related to management of substance use disorders. There was no statistically significant difference in groups divided on the base of age or experience of respondents.Conclusion: In southern Punjab, Pakistan, while most GPs agree about the seriousness of substance abuse disorders, majority are not well trained in tackling it and don’t feel confident in managing patients related to addiction. There is a dire need for revision courses, lectures and workshops related to this topic for our general practitioners and family physicians on both private and public fronts.